2014
DOI: 10.1002/jcp.24694
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular MMP‐2 Activity in Skeletal Muscle Is Associated With Type II Fibers

Abstract: Matrix metalloproteinase 2 (MMP-2) is a proteolytic enzyme implicated in motility, differentiation and regeneration of skeletal muscle fibers through processing of extracellular substrates. Although MMP-2 has been found to be localized intracellularly in cardiomyocytes where the enzyme is thought to contribute to post-ischemic loss of contractility, little is known about intracellular MMP-2 activity in skeletal muscle fibers. In the present study we demonstrate intracellular MMP-2 in normal skeletal muscle by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
(67 reference statements)
0
23
1
Order By: Relevance
“…Numerous genes with structural, motor and regulatory functions were highly expressed in BFxT compared to Texel bicep muscle, with approximately 5- to 18-fold expression increases for various members of the collagen ( COL1A1 , COL1A2 , COL3A1 ) and myosin families ( MYH2 , MYL4 ), along with CSRP3 (a mechanosensor) [98], FMOD (fibromodulin, a regulator of fibrillogenesis) [99], keratocan ( KERA , a proteoglycan involved in myoblast differentiation) [100], matrix metalloproteinase 2 ( MMP2 , a proteolytic enzyme associated with muscle regeneration) [101], and calsequestrin 2 ( CASQ2 , one of the most abundant Ca 2+ -binding proteins in the sarcoplasmic reticulum, essential for muscle contraction) [102].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous genes with structural, motor and regulatory functions were highly expressed in BFxT compared to Texel bicep muscle, with approximately 5- to 18-fold expression increases for various members of the collagen ( COL1A1 , COL1A2 , COL3A1 ) and myosin families ( MYH2 , MYL4 ), along with CSRP3 (a mechanosensor) [98], FMOD (fibromodulin, a regulator of fibrillogenesis) [99], keratocan ( KERA , a proteoglycan involved in myoblast differentiation) [100], matrix metalloproteinase 2 ( MMP2 , a proteolytic enzyme associated with muscle regeneration) [101], and calsequestrin 2 ( CASQ2 , one of the most abundant Ca 2+ -binding proteins in the sarcoplasmic reticulum, essential for muscle contraction) [102].…”
Section: Resultsmentioning
confidence: 99%
“…Deus et al [10] analyzed the tibialis anterior muscle which is primarily fast-twitch in rats [33], while our study used gastrocnemius muscle. Recently, Hadler-Olsen et al [12] reported that the predominance of glycolytic fibers favors the increase in enzyme activity. However, evidence suggests that the gastrocnemius muscle is more oxidative than the tibialis anterior [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intracellular localization of MMP‐2 has been reported in various cell types and injury models . Our previous studies with H9C2 cardiomyocytes demonstrated that the NTT‐MMP‐2 isoform was generated by oxidative stress‐mediated activation of an alternate promoter within the first intron of the MMP‐2 gene .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intracellular localization of MMP-2 has been reported in various cell types and injury models. [27][28][29] Our previous studies with H9C2 cardiomyocytes demonstrated that the NTT-MMP-2 isoform was generated by oxidative stress-mediated activation of an alternate promoter within the first intron of the MMP-2 gene. 17,18 NTT-MMP-2 lacks both the secretory sequence and the inhibitory prodomain, and thus remains exclusively intracellular and is enzymatically active.…”
Section: Discussionmentioning
confidence: 99%